The Relationship between the Husband's Role and the Readiness of Third-Trimester Pregnant Women in Facing Childbirth During the New Normal Period of Covid-19 - Resi Wiliam Leastuti; Mega Silvian Natalia; Agustina Widayati (Health and Technology Journal (HTechJ), 2023)
Covid-19 is a group of viruses that can cause disease in animals or humans. Several types of coronaviruses cause respiratory tract infections in humans ranging from cold coughs to more serious ones, such as Middle East Respiratory Syndrome (MERS) and severe acute respiratory syndrome (SARS). This study analyzes the relationship between the husband's role and the readiness of third-trimester pregnant women to face childbirth during the new normal period in the work area of ​​the Kuripan Health Center, Probolinggo Regency. This quantitative research design uses a correlational design using a cross-sectional study approach with 32 respondents using an accidental sampling technique. Data collection included coding, editing, and tabulating, then analyzed manually and by computer with the Wilcoxon test. Based on 32 respondents, primarily the role of a good husband, 12 respondents (37.5%) including the readiness of third-trimester pregnant women who were ready, ten respondents (31.3%) and pregnant women who were not prepared for childbirth, two respondents (6.3%). It was obtained as p=0.007, so there is a relationship between the husband's role and the readiness of third-trimester pregnant mothers to face delivery on the new normal in the work area of ​​the Kuripan Health Center, Probolinggo Regency. It is expected that during the examination of pregnant women before delivery in every village for 36 weeks of gestation, a swab antigen test will be carried out once and before delivery once so that sometimes the role of the husband and family influences the mother's readiness to carry out the prenatal examination process, especially during the transition period from pandemic to new normal.